Sams Teach Yourself Internet and Web Basics All in One - Snell, Ned (Sams, 2011)
Find all the answers to a new Internet user's questions in one big, easy-to-use book. Sams Teach Yourself Internet and Web Basics All in One is designed to teach he new computer user how to easily work with a variety of digital media. It does not assume the reader wants to learn how to use just one product, but covers multiple products and technologies in a logical fashion. Topics covered include: Internet Basics, Choosing a Service, Web Browsing, Email and Chat, Fun and Games, Stopping Viruses and Hackers, and Creating Web Pages. If you are a beginning Internet user who wants to buy one, single book to help you better use your Internet and your computer, or accomplish a broad range of computer activities Sams Teach Yourself Internet and Web Basics All in One is the book for you!